"ADMINISTRATIVE CONSTITUTIONALISM": CONSIDERING THE ROLE OF AGENCY DECISION-MAKING IN AMERICAN CONSTITUTIONAL DEVELOPMENT. Issue 1 (2021) - Bernstein, David E.
Abstract: The last decade or so has seen an explosion of scholarship by American law professors on what has become known as administrative constitutionalism. Administrative constitutionalism is a catchphrase for the role of administrative agencies in influencing, creating, and establishing constitutional rules and norms, and governing based on those rules and norms. Though courts traditionally get far more attention in the scholarly literature and the popular imagination, administrative constitutionalism scholars show that administrative agencies have been extremely important participants in American constitutional development. Section I of this essay identifies three different versions of administrative constitutionalism—(1) Engagement with Existing Constitutional Doctrine; (2) Resolving Questions of Statutory Meaning that Implicate Constitutional Questions; and (3) Shadow Administrative Constitutionalism—and provides examples from the scholarly literature to illustrate these distinct manifestations of administrative constitutionalism. Section II of this essay discusses the normative turn in administrative constitutionalism scholarship. Much of this normative literature is implicitly or explicitly premised on the notion that agencies are more likely to pursue progressive goals than are other government actors. Section III of this essay disputes the notion that agency constitutional decision-making is "democratic" and that agencies are naturally inclined to serve progressive goals. Finally, Section IV of this essay notes that scholars who support broad agency autonomy to work out and enforce their own constitutional visions have failed to consider how their work fits in with the economic and political science literature on agency behavior. One can predict, based on that literature, that agencies given broad autonomy under the guise of administrative constitutionalism will primarily be inclined to expand their scope and authority at the expense of countervailing considerations.